miR-30b-3p Inhibits Proliferation and Invasion of Hepatocellular Carcinoma Cells via Suppressing PI3K/Akt Pathway - Gao, Dongkai; Zhou, Zumo; Huang, Heqing (Frontiers in Genetics, 2019)
Background: The micro-RNA miR-30b-3p has been reported to play a crucial role in several cancers. However, the biological function of miR-30b-3p in hepatocellular carcinoma (HCC) is still unknown. Methods: RT-qPCR was employed to determine the expression of miR-30b-3p in HCC tissues and cells. The MTT assay, colony formation assay, and cell migration and invasion assay were employed to evaluate the role of miR-30b-3p in HCC cells. A dual-luciferase reporter assay was employed to verify the target of miR-30b-3p. Western blotting was employed to determine the expression of key molecular signal transducers along TRIM27-PI3K/Akt axis. Results: Expression of miR-30b-3p was markedly decreased in HCC tissues and cells and positively correlated with higher overall survival. Moreover, miR-30b-3p overexpression significantly repressed cell viability, proliferation, migration, and invasion of HCC cells in vitro. Notably, we demonstrated that miR-30b-3p directly bound to the 3′-untranslated region of tripartite motif containing 27 (TRIM27) mRNA by downregulating the expression of TRIM27, which was demonstrated to be negatively correlated with miR-30b-3p expression. TRIM27 was demonstrated to have an oncogenic role in HCC cells by enhancing cell viability, proliferation, migration, and invasion. Finally, the miR-30-3p-TRIM27-PI3K/Akt axis was shown to play a crucial role in HCC cells in vitro. Conclusion: Our results indicated that miR-30-3p might act as a new biomarker for the future diagnosis and treatment HCC.